Internal friction and frequency measurements in molybdenum containing oxygen and nitrogen - Grandini, Carlos Roberto [UNESP]; Capelli, M. R.; Florencio, O.; Tejima, H.; Jordao, JAR (Editions Physique, 1996)
We have measured internal friction and frequency as a function of temperature in molybdenum containing oxygen and nitrogen in solid solution. These measurements were performed by a torsion pendulum operating in the temperature range of 300 K to 700 K with oscillation frequency about 1.0 Hz. The results showed the complex relaxation process identifying the stress induced ordering of oxygen and nitrogen atom around the molybdenum atoms of the metallic matrix.